CLINICAL SPECTRUM OF MACULAR-FOVEAL CAPILLARIES EVALUATED WITH OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 3 (March 2017) - Cicinelli, Maria V.; Carnevali, Adriano; Rabiolo, Alessandro; Querques, Lea; Zucchiatti, Ilaria; Scorcia, Vincenzo; Bandello, Francesco; Querques, Giuseppe
Abstract : Purpose: To describe macular-foveal capillaries (MFC) by means of optical coherence tomography angiography and to identify the clinical spectrum of this angiographic feature. Methods: Patients with MFC presenting at the Medical Retina & Imaging Unit of the Department of Ophthalmology, University Vita-Salute San Raffaele in Milan were recruited. Patients underwent a complete ophthalmologic examination that included slit-lamp examination, fundus examination, measurement of best-corrected visual acuity, fundus autofluorescence, and spectral-domain optical coherence tomography (Spectralis HRA + OCT; Heidelberg Engineering, Heidelberg, Germany). Fluorescein angiography was performed in selected cases. Optical coherence tomography angiography was performed through Zeiss prototype (AngioPlex, CIRRUS HD-OCT models 5000; Carl Zeiss Meditec, Inc, Dublin, OH). Results: Twelve eyes of 10 consecutive white patients (5 men and 5 women; 50%) presenting MFC were included. Mean age was 66.2 ± 10.2 years (range, 53–79 years); mean best-corrected visual acuity was 0.1 ± 0.13 logarithm of the minimum angle of resolution (range, 0–0.4 logarithm of the minimum angle of resolution, corresponding to 20/20 to 20/50). Mean central macular thickness was 348 ± 57.6 μ m. Two patients were affected by macular pucker, two by postsurgical macular edema, two by age-related macular degeneration, one by diabetic retinopathy, one by dome-shaped macula, one presented with chronic serous chorioretinopathy, and one with branch artery occlusion. Six eyes disclosed a complete absence of the foveal avascular zone, whereas the six other cases showed a partial foveal avascularity. No significant difference was found between complete and incomplete MFC with regards to best-corrected visual acuity ( P = 0.272) and central macular thickness ( P = 0.870). Conclusion: Cases of persistent MFC are heterogeneous in demographic characteristics, fundus appearance, and visual function. However, MFC, presenting either as complete absence of the foveal avascular zone or only partial foveal avascularity, may complicate different retinal abnormalities or represents a coincident finding. Abstract : This study describes macular-foveal capillaries by means of optical coherence tomography angiography as heterogeneous in demographic characteristics, fundus appearance, and visual function. Macular foveal capillaries, presenting either as complete absence of the foveal avascular zone or as only partial foveal avascularity, may complicate different common retinal abnormalities or represents a coincident finding.